2018
DOI: 10.1007/s00210-018-1498-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of vinpocetine against neurotoxicity of manganese in adult male rats

Abstract: Manganese (Mn) is required for many essential biological processes as well as in the development and functioning of the brain. Extensive accumulation of Mn in the brain may cause central nervous system dysfunction known as manganism, a motor disorder associated with cognitive and neuropsychiatric deficits similar to parkinsonism. Vinpocetine, a synthetic derivative of the alkaloid vincamine, is used to improve the cognitive function in cerebrovascular diseases. It possesses antioxidant and antiinflammatory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 96 publications
1
13
1
Order By: Relevance
“…Our findings also agree with earlier findings on the ability of plant alkaloid extracts to ameliorate Mn-induced impairment in the locomotor performance and survival rate of D. melanogaster [14, 38]. Furthermore, it has also been reported that plant alkaloid extract ameliorated Mn-induced neurotoxicity in rats [39, 40].…”
Section: Resultssupporting
confidence: 93%
“…Our findings also agree with earlier findings on the ability of plant alkaloid extracts to ameliorate Mn-induced impairment in the locomotor performance and survival rate of D. melanogaster [14, 38]. Furthermore, it has also been reported that plant alkaloid extract ameliorated Mn-induced neurotoxicity in rats [39, 40].…”
Section: Resultssupporting
confidence: 93%
“…The antiapoptotic effect of vinpocetine against renal IRI may be due to direct inhibition of activated caspase-3 or indirectly due to its antioxidant and anti-inflammatory effects. [68,69]…”
Section: Discussionmentioning
confidence: 99%
“…Vinpocetine, a synthetic derivative of the vinca alkaloid vincamine, attenuated Mn-induced oxidative stress and apoptosis in rats ( Nadeem et al, 2018 ) and NE-4C cells ( Bora et al, 2016 ). D-ribose-L-cysteine, a cysteine analog exhibiting antioxidant properties, attenuated Mn-induced oxidative stress and toxicity by enhancing CAT and SOD activity in rats ( Akingbade et al, 2022 ).…”
Section: Neurotherapeutics and Their Potential Underlying Mechanisms ...mentioning
confidence: 99%